2007
DOI: 10.1142/s0218271807009309
|View full text |Cite
|
Sign up to set email alerts
|

Five-Dimensional Dust Collapse With Cosmological Constant

Abstract: We study the five-dimensional spherical collapse of an inhomogeneous dust in the presence of a positive cosmological constant. The general interior solutions, in the closed form, of the Einstein field equations, i.e. the 5D Tolman-Bondi-de Sitter, is obtained which in turn is matched to the exterior 5D Schwarzschild-de Sitter. It turns out that the collapse proceeds in the same way as in the Minkowski background, i.e. the strong curvature naked singularities form and thus violate the cosmic censorship conjectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…where W = W (r) is an arbitrary function of r. Note the striking similarity of function A with analogous 5D-LTB solutions [18,20,21]. In what follows we shall consider the case A(t, r) = R ′ /W , since in the other case the α → 0 leads to a trivial solution.…”
Section: D Lemaitre-tolman-bondi Solutions In Einstein Gauss-bonmentioning
confidence: 98%
“…where W = W (r) is an arbitrary function of r. Note the striking similarity of function A with analogous 5D-LTB solutions [18,20,21]. In what follows we shall consider the case A(t, r) = R ′ /W , since in the other case the α → 0 leads to a trivial solution.…”
Section: D Lemaitre-tolman-bondi Solutions In Einstein Gauss-bonmentioning
confidence: 98%
“…The solution for B(r, t) in Eq. (10) is similar to 5D-LTB solution [39,40,41], while solution in Eq. (11) is trivial for α → 0, hence we take non-trivial form of B(r, t) given in Eq.(10).…”
Section: Exact Solution Of Field Equations In Einstein Gauss-bonnet Gmentioning
confidence: 76%
“…(14) is not always a unique choice for p(t). For example it can be treated with c = 0, but such choices do not provide the results in closed form which reduce to 5D dimensional perfect fluid collapse in the limit α → 0 [33,40,41], and not recover the results of 5D dust collapse in Einstein Gauss-Bonnet gravity as p → 0 [37]. That is why we have taken the pressure as constant which is a better choice in the present situation.…”
Section: Exact Solution Of Field Equations In Einstein Gauss-bonnet Gmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that constant specific heat (C.S.H) approximation 24,25,26 widely used in standard thermodynamics, is applicable to the multifractal data too. Nearly constant values of multifractal specific heat have been observed from the analysis of the experimental data on hh and AA collisions 12,27,28,29,30,31 ; the analysis has been carried out following the method proposed by Takagi 23 .…”
Section: Introductionmentioning
confidence: 99%